An Analytical Study of The Reality of Economic Diversification in Algeria During the Period (2010-2023) - Imene SOUAHLIA; Khemissi GAIDI; Imane MELALA (Dirassat Journal Economic Issue, 2025)
This research aims to diagnose the reality of economic diversification in Algeria as a country that heavily relies on oil rent revenues. In our study, we addressed the concept of economic diversification and its forms, as well as reviewed the requirements for activating the economic diversification policy. We reached a set of results, the most important of which is that the economic diversification policies that Algeria has adopted have achieved relative success despite the weak growth in economic indicators. To achieve real and sustainable diversification, it is necessary to support economic structural reforms, in order to build and establish new industries in various sectors with economic value. The study also recommended the need to diversify exports of goods, diversify sources of revenue, and reduce reliance on financing through oil royalties.